Surgical and clinical impacts of mixed reality-guided glioblastoma resection versus standard neuronavigation: improving tumor surgery - Haemmerli, Julien; Khatchatourov, Samuel; Chaboudez, Etienne; Roth, Leonard; Sandralegar, Abiram; Janssen, Insa; Migliorini, Denis; Schaller, Karl; Bijlenga, Philippe (Frontiers in Oncology, 2025)
BackgroundGlioblastomas (GBM) are typically treated with surgery and radio-chemotherapy, with patient survival often depending on the extent of tumor resection. This study compares outcomes of GBM surgery using 5-ALA, intraoperative neuroelectrophysiology, and neuro-navigation, either in a standard setting (STD) or enhanced by mixed reality (MR) guidance.MethodsThis retrospective study included GBM patients who underwent resection at Geneva University Hospitals between 2015 and mid-2022, excluding biopsies and partial debulking. Primary outcomes included postoperative residual tumor volume (RV) based on postoperative contrast uptake on the MRI, while secondary outcomes were gross total resection (GTR), extent of resection (EOR), new postoperative deficits, overall survival (OS), progression-free survival (PFS), and Karnofsky performance scores. Confounding factors such as intraoperative monitoring and use of fluorescence were analyzed.ResultsOf 115 patients, 76 were in the STD group and 39 in the MR group, with comparable demographics. The MR group had significantly lower RV (median 0.01 cm³ vs. 0.34 cm³, p=0.008) and higher GTR rates (median 50% vs. 26.7%). EOR was also superior in the MR group (median 99.9% vs. 98.2%, p=0.002). New focal deficits occurred in 39% (STD) and 36% (MR) of cases (p=0.84). While median OS was not significantly different (475 vs. 375 days, p=0.63), median PFS was longer in the MR group (147 vs. 100 days, p=0.004).ConclusionMR guidance improves the quality of tumor resection and enhances progression-free survival without increasing postoperative deficits, although it does not significantly impact overall survival.